PENINGKATAN KAPASITAS MASYARAKAT MELALUI EDUKASI PEMBIBITAN NILAM (POGOSTEMON CABLIN BENTH.) DI DESA NGLEGOK, KARANGANYAR - Yusuf Dhanzky Handitra; Iqbal Tora Hakeem; Alfira Widya Sari; Aqila Aliya Mahesha; Imron Alimudin; Jihaan Nuhaa Haniifah; Nadia Ramadhanti; Sarita Ayu Aprilia; Nabila Firly Aulia; Yohanes Paulus Jujur Kinanthi; Supriyadi Wibowo (Jurnal Riset Multidisiplin Edukasi, 2026)
Patchouli (Pogostemon cablin Benth.) is a strategic commodity producing essential oil with high economic value; however, its productivity at the farmer level is still constrained by low seedling quality and limited technical knowledge of propagation. This problem is also encountered by the community of Nglegok Village, which has considerable potential for patchouli development as a source of local economic growth. This study aims to examine the effect of educational activities and practical training on patchouli propagation in improving the knowledge and skills of the village community. The research employed a qualitative approach using participatory observation, unstructured interviews, and documentation involving residents who participated in socialization and patchouli propagation practices. The results indicate that education delivered through visual materials and hands-on practice significantly improved community understanding of proper cutting selection, preparation of porous growing media, use of shading, and the importance of tool sanitation. The impact of the activity is reflected in increased community capacity and self-reliance in conducting independent propagation, as well as growing awareness of value-added downstream opportunities for patchouli-based products. The study concludes that patchouli propagation education is effective as an initial step in strengthening village economies based on local potential. Therefore, further assistance at the stages of cultivation, distillation, and processing of derivative products is recommended to ensure sustainable economic benefits.